Politics and governance in Nepal - Sharma, Kishor (2012)
This article discusses the role that politics and governance have played in the current state of affairs in Nepal, citing a lack of vision among political leadership and their inability to understand the consequences of socioeconomic exclusion as the roots of the current political crisis in Nepal. It outlines the resultant problems of the centralisation of power, corruption, a bias towards urban development and especially the historical exclusion of minority and underprivileged classes from participation in governance and mainstream politics. It is argued that there is a need to introduce bold reforms in economic policy, politics and the institutional setup to sustain growth and increase the collective voice and bargaining power for all disadvantaged groups. - Reproduced.
Keywords: Public administration - Nepal; Public administration